2021
DOI: 10.17576/gema-2021-2101-06
|View full text |Cite
|
Sign up to set email alerts
|

Ludic Adaptation: Can We Babyfy, Chibify, Bambify, or Cherubify a Literary Text for Younger Audiences?

Abstract: Studies on adaptation for younger audiences tend to mull over around the film adaptation of children classics. Adaptation of textual, visual, and operative elements for younger audiences in the context of literary texts with ergodicity like apps, comics, animation films, and games is understudied. This case study based descriptive qualitative study aims at exploring and investigating the phenomenon and how this adaptation is exercised. This study employs Siddharthan's text simplification, Genette's hypertextua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These clickable comments and notes contain religious lessons from the Qur'an and hadith or religious commentaries from trustworthy Islamic scholars through medial modification. This medial modification, changes on the media used to transfer particular information, involves what is called as ludic adaptation, where media is adapted and adjusted for younger audiences (Purnomo et al, 2021). Clicking the comments and notes, children could read and listen to the commentaries and notes regarding with particular events of the story.…”
Section: Paratextualizationmentioning
confidence: 99%
“…These clickable comments and notes contain religious lessons from the Qur'an and hadith or religious commentaries from trustworthy Islamic scholars through medial modification. This medial modification, changes on the media used to transfer particular information, involves what is called as ludic adaptation, where media is adapted and adjusted for younger audiences (Purnomo et al, 2021). Clicking the comments and notes, children could read and listen to the commentaries and notes regarding with particular events of the story.…”
Section: Paratextualizationmentioning
confidence: 99%
“…This is because the three of them cannot be separated from text. Purnomo et al (2021), in tehir journal article discussing Ludic Adaptation, implies that the essence of these three theories, transstylization, intertextuality, and adaptation, is to see the changes that exist from previous literary works to the most recent literary works.…”
Section: Transstylizationmentioning
confidence: 99%
“…Transstylization is concerned with the preparation of a text. The point here is that the text can be adapted to different media, and transstylization is focusing on the study of the change with content as the focus (Purnomo, et al, 2021).…”
Section: Transstylizationmentioning
confidence: 99%
“…The localization is acceptable since it fits with the sarcastic comedy of the game. This ludic phenomenon in the context of translation studies, as indicated by Purnomo et al (2021), Guyker Jr. (2016, Purnomo et al (2016), and Schules (2012), is more perceptible from translation exercised by fans or what is called as fan translation. This translation type which is also known as user generated translation (Ding et al, 2021) covers a wide range of translation type from comics scanlation (Inose, 2012), fansubbing (Massidda, 2015), fandub (Baños, 2020), and rom hacking or fan localization (Consalvo, 2013).…”
Section: Introductionmentioning
confidence: 98%